Examining Effects of the COVID-19 National Lockdown on Ambient Air Quality Across Urban India - Chimurkar Navinya; Girish Patidar; Harish C. Phuleria (Aerosol and Air Quality Research)
Abstract Lockdown seems the most effective way to prevent the spread of Coronavirus disease (COVID-19) as no vaccine is currently available in the market to cure it. Thus, India has enforced nation-wide lockdown from 25th March to lower the spread of this contagious virus and associated illness. This study aims to quantify the changes in pollution levels as well as meteorology during the 6-weeks COVID-19 lockdown over 17 cities of India for 5 major criteria pollutants using publicly available air quality data. Hourly averaged data is accessed from the air quality monitoring stations during the lockdown and immediate pre-lockdown periods and also corresponding data from the previous year (2019). During the lockdown, PM2.5, PM10, NO2, and CO reduced significantly with relatively small changes in meteorological conditions compared to the pre-lockdown period. The highest decline is observed over Ahmedabad (68%), Delhi (71%), Bangalore (87%), and Nagpur (63%) for PM2.5, PM10, NO2, and CO, respectively. The Northern region shows the highest decline for all the pollutants with most days below NAAQS during lockdown—86%, 68%, and 100% compared to 18%, 0%, and 38% in 2019 for PM2.5, PM10, and NO2, respectively. The smaller cities Dewas and Jorapokhar show lesser improvement with only 3% and 16% improvement in days under NAAQS for PM2.5. SO2 is the least affected pollutant with little improvement. The major decline is observed during 7–10 am and 7–10 pm hours of the day for PM2.5, PM10, NO2, and CO with more than 40% reduction. The meteorological changes are very small and heterogeneous over India showing a similar extent of changes compared to the previous year but the pollution levels have reduced significantly. Thus, the sharp decline in pollutant concentration during the ~6 weeks period national lockdown can be attributed to the reduced economic and transport activities.